2020
DOI: 10.1007/s10603-019-09444-x
|View full text |Cite
|
Sign up to set email alerts
|

Retirement Financial Behaviour: How Important Is Being Financially Literate?

Abstract: Using Item Response Theory to analyse survey data from a representative sample of 551 Swedish citizens, a new 16-question measure of fact-based financial literacy is developed and validated. Uni-dimensionality of the measure is verified, and expected correlations are observed with an existing measure of fact-based financial literacy, a measure of subjective financial literacy or confidence, and age, gender, and income. A significant impact of fact-based and subjective financial literacy are found on three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 61 publications
4
42
0
2
Order By: Relevance
“…This research provides the basis for several further developments which could consider the role of other individual-level characteristics as personality traits, overconfidence, experience, risk attitude, numeracy, financial literacy (Hauff et al 2020), graph literacy (Okan et al 2016) in modulating information processing, and product evaluations. Moreover, future studies might explore other phases of the decision-making rather than visual attention and observe behaviour related to actual choice.…”
Section: Discussionmentioning
confidence: 96%
“…This research provides the basis for several further developments which could consider the role of other individual-level characteristics as personality traits, overconfidence, experience, risk attitude, numeracy, financial literacy (Hauff et al 2020), graph literacy (Okan et al 2016) in modulating information processing, and product evaluations. Moreover, future studies might explore other phases of the decision-making rather than visual attention and observe behaviour related to actual choice.…”
Section: Discussionmentioning
confidence: 96%
“…The use of IRT to construct scales can facilitate precisely such an effort through the shared use of common “anchor” items with known existing parameter values. We concur with Huston (2010) and others (Knoll and Houts, 2012; Hauff et al ., 2020) in advocating this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions were drawn by Yilmazer and Scharff (2014) and Thalassinos et al (2019) whose research showed that financial planning for retirement is a lifelong process which may be constrained by financial literacy and competing demands for resources across one's life course. Hauff et al (2020) demonstrated that financial literacy potentially influences retirement financial behaviour entailing planning, saving, and investment management. This paper also considers other factors determining savings-related financial behaviour, including saving for old age.…”
Section: Literature Reviewmentioning
confidence: 99%